Herbal Extract Nano-formulation for Huntington’s disease Treatment - Patil, Sapana A. (Asian Journal of Pharmaceutics (AJP), 2024)
The hallmark of Huntington’s disease (HD), an autosomal dominant genetic disorder, is degeneration of neurons of central nervous system (CNS). Tranquilizers, antipsychotics, antidepressants, and monoamine depletors are among the often utilized in treatments. These medications, however, are unable to stop the behavioral, cognitive, and psychotic disorders linked to HD. Moreover, their long-term negative effects restrict their continuous use. Still, due to their limited drug solubility and penetration to the target site, herbal medicines are unable to advance the phase of clinical investigation. Herbal formulation and extracts that show potential in neurotoxic HD models must have their active ingredients and underlying mechanisms of action thoroughly investigated. Several plants that are known to be CNS-active medications, such as Bacopa monnieri, Ginkgo biloba, Panax ginseng, Cannabis sativa, and Curcuma longa L. were listed as the most promising anti-HD options. In the past few decades, it has been a paradigm shift in research toward the creation of nanoformulations based on herbal medications that can improve their permeability through blood-brain barrier and bioavailability. This review addresses the phytomedicines investigated against HD, current clinical studies on herbal medications used only for HD treatment, and the possible neuroprotective effects of these drug’s nanocarriers.